(untitled) (Journal of Parents and Teachers, 2024)
The article discusses the impact of environmental stress on human health, highlighting how factors such as noise, temperature and overcrowding can trigger adverse physiological and psychological reactions. The phases of stress reaction are described: alarm, resistance and exhaustion, and effects such as anxiety, depression and physical problems are listed. In addition, the importance of learning techniques for managing stress and adapting to difficult situations is emphasized.